OPTIMIZING PARTICIPATORY APPROACH THROUGH MEMRISE APP IN VOCABULARY ENHANCEMENT FOR INDONESIAN STUDENTS - Wuisan, Nicole Jeanine; Simanjuntak, Debora Chaterin (Universitas PGRI Sumatera Barat, 2023)
The participatory method is a well-established strategy approved by researchers and is regarded as essential for teaching English as a second language. The Memrise application is employed as a supplementary learning tool to make English classes engaging and captivating. Consequently, the objective of this research is to assess whether a significant disparity exists in vocabulary improvement between two Junior High School classes when using the Participatory Approach and Memrise. The research methodology applied here is quantitative, utilizing a comparative design comprising pre-tests and post-tests. Both classes are under the instruction of the same teacher (the researcher), but they employ different teaching methods. The 7A class is instructed through the participatory approach combined with the Memrise application, while the other class is taught using the conventional homeroom teacher method. Notably, both classes demonstrated improved vocabulary, but the 7A class exhibited a notably higher level of enhancement compared to the 7B class. Moreover, the results indicate a significant discrepancy in vocabulary enhancement between students taught using the participatory approach and the Memrise application versus other methods which is shown through the average increase of the 7A class is 90% and the average increase of the 7B class is 39%. To summarize, the findings underscore the effectiveness of the Participatory Approach and Memrise in facilitating vocabulary enrichment and enhancement among students.